A Study of Correlation of Adiponectin Levels in Metabolic Syndrome - Apurv Singhal; Vedpal Singh Punia; Akash Bharti; Shaavi Mittal; Praveen Raman Mishra; Prem Kuma (European Medical Journal)
Introduction: Metabolic syndrome (MetS), also known as insulin resistance syndrome, is described as a cluster of cardiometabolic symptoms such as high blood pressure, elevated fasting glucose, or insulin resistance. MetS is one of the most serious public health problems being faced globally. The purpose of the current investigation was to determine its prevalence, as well as the relationship between blood adiponectin levels and the development of MetS. Materials and Methods: This observational cross-sectional hospital-based study was performed in the Department of General Medicine, School of Medical Sciences and Research, Sharda Hospital, Greater Noida, Uttar Pradesh, India, from January 2019–June 2020. Sixty patients attending the medicine out- or inpatient department, who confirmed consent, and fit into the International Diabetes Federation (IDF) inclusion criteria for MetS, were recruited for this study. The final sample size for this study was found to be 60, with a prevalence of 10%. This is the reason the study’s precision decreased to ±7.6%, implying that the precision of the end result may vary by ±7.6%. Results: Subjects without MetS were on average younger, had a lower BMI, and had a smaller waist circumference than those who had MetS, according to the findings. They also had lower blood pressure, pulse rate, and fasting plasma glucose levels than the people with MetS, and there were statistically significant variations in lipid profiles between those with and without MetS. In people who did not have MetS, the mean serum adiponectin concentration was 15.79±2.90 mg/mL, whereas the mean serum adiponectin concentration in people who did have MetS was 11.02±2.63 mg/mL (p<0.001). The levels of adiponectin were compared with the different components of MetS as defined by the IDF. The mean adiponectin concentrations in connection to the clinical characteristics of MetS are shown in Table 1 . The authors discovered that lower adiponectin levels were statistically significantly linked with the majority of the characteristics. In a multivariate analysis, the serum adiponectin content was found to be significantly inversely associated to systolic blood pressure (r=-0.262; p<0.050), BMI (r=-0.288; p<0.050), total cholesterol (r=-0.515; p<0.001), and low-density lipoprotein (r=-0.305; p<0.050) in the study participants. Conclusion: In conclusion, the present results suggest that circulating levels of adiponectin are reduced in the presence of MetS.